Understanding the Healthcare Practitioners’ Experience in Managing Women with Postnatal Depression: A Qualitative Study in Malaysia - Mohd Arifin, Siti Roshadai; Abang Abdullah, Khadijah Hasanah; Abas, Nurul Ain Hidayah; Husain, Rohayah; Che Man, Mohamad (IIUM Medical Journal Malaysia, 2022)
INTRODUCTION: Postnatal depression is largely underdiagnosed in many low-and middle-income countries, including Malaysia. Healthcare practitioners’ perceptions towards postnatal depression were identified as one of the main barriers to seeking help. Objective: This study aimed to explore the perceptions of healthcare practitioners about postnatal depression, and their experience in managing women with postnatal depression in Malaysia. Materials and methods: Eighteen healthcare practitioners (5 head nurses, 9 nurses, and 4 doctors) working in maternal and child health clinics and a female psychiatric ward in Kuala Lumpur were individually interviewed following a generic qualitative research design. Interview data were transcribed verbatim, and the transcripts were analyzed using framework analysis. Results: Healthcare practitioners reported that their management of women with postnatal depression was limited by the absence of a specific screening tool, and presence of stigma associated with postnatal depression. Discussion and conclusion: Healthcare practitioners were found to be aware of poor maternal mental health provision within their clinical setting and are ready to contribute to developing protocols to improve maternal mental health. As its diagnosis and treatments vary from general depression, there should be a specific direction addressed in the policy to assist in actions for managing postnatal depression. Professional training and continuous education on postnatal depression are a fundamental component in fostering quality of care, and public awareness as well as improving stigma within the Malaysian healthcare system.